ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WORDS OF MOUTH (Studi Empirik Pada Pelanggan Kentucky Fried Chicken Di Semarang) - Kusnan, Cindy Lestari (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2012)
The increasing competition in all of business industry areas are affecting the fast food restaurant business. Although Kentucky Fried Chicken (KFC) is marked a fast-food restaurant market leader, based on survey data from SWA business magazine, in 2012 KFC’s words of mouth which have declined. Due to some inconsistencies among previous studies about the customer satisfaction on words of mouth, the further research is required.This study aims to analyze how to increase words of mouth through the management of customer satisfaction by adding an intervening variable which was customer loyalty. The purpose of this study was to analyze the influence of advertising appeal, brand image, customer satisfaction, positive attitude toward the brand, customer loyalty and words of mouth in customer consideration purchasing KFC’s products. Respondent used in this study were the customers of KFC which were 120 respondents. The theoretical model consisted of six variables with six hypotheses and were tested by using SEM analytic tools by using AMOS program.The findings of this study showed that five hypotheses were accepted and one of them was rejected which was the third hypothesis. Third hypothesis stated that the higher of brand image affects on higher words of mouth could not be statistically proven or rejected. Thus, it could be concluded that the variable of brand image can not increase the performance of customer loyalty. Therefore, it is suggested that the increasing of words of mouth is more focused on the increasing customer loyalty from customer satisfaction, also advertising appeal and brand image which can increasing positive attitude toward the brand so it is expected this condition will influence the increasing of words of mouth.